Mitochondrial Oxidative Phosphorylation in Viral Infections - Neeraja Purandare; Esha Ghosalkar; Lawrence I. Grossman; Siddhesh Aras (Viruses, 2023)
Mitochondria have been identified as the “powerhouse” of the cell, generating the cellular energy, ATP, for almost seven decades. Research over time has uncovered a multifaceted role of the mitochondrion in processes such as cellular stress signaling, generating precursor molecules, immune response, and apoptosis to name a few. Dysfunctional mitochondria resulting from a departure in homeostasis results in cellular degeneration. Viruses hijack host cell machinery to facilitate their own replication in the absence of a bonafide replication machinery. Replication being an energy intensive process necessitates regulation of the host cell oxidative phosphorylation occurring at the electron transport chain in the mitochondria to generate energy. Mitochondria, therefore, can be an attractive therapeutic target by limiting energy for viral replication. In this review we focus on the physiology of oxidative phosphorylation and on the limited studies highlighting the regulatory effects viruses induce on the electron transport chain.